Interphase boundary layer-dominated strain mechanisms in Cu+ implanted Zr-Nb nanoscale multilayers. (1st January 2021) - Daghbouj, N.; Callisti, M.; Sen, H.S.; Karlik, M.; Čech, J.; Vronka, M.; Havránek, V.; Čapek, J.; Minárik, P.; Bábor, P.; Polcar, T.
Abstract: Sputter-deposited Zr/Nb nanoscale metallic multilayers with a periodicity of 27 (thin) and 96 nm (thick) were subjected to Cu + implantation with low and high fluences and then studied using various experimental techniques in combination with DFT calculations. After Cu + implantation, the thinner multilayer exhibited a tensile strain along c-axis in Nb layers and a compressive strain in Zr layers, while the thicker multilayer showed a compressive strain in both layers. The strain is higher in the thin multilayer and increases for higher fluences. We developed a mathematical method for the fundamental understanding of the deformation mechanisms in metallic multilayers subjected to radiation damage. In the model, the cumulative strain within a layer is described as the combination of two contributions coming from the interfacial region and the inner region of the layers. The semi-analytical model predicts that the interfacial strain is dominant and extends over a certain region around the interface. Predictions are well supported by ab-initio calculations which show that in the vicinity of the interface and in the Zr side, vacancies and interstitials (low energy barriers) exhibit high mobility compared to the Nb side, thus resulting in a high recombination rate. As a consequence, less strain occurs in the Zr side of the interface compared to the Nb side. The density and distribution of various types of defects along the ion profile (low and high damaged regions) are obtained by combining DFT results and the predictions of the model. Graphical abstracts: Image, graphical abstract